Analysis of Building Energy Savings Potential for Metal Panel Curtain Wall Building by Reducing Thermal Bridges at Joints Between Panels. (September 2016) - Oh, Jung-Min; Song, Jin-Hee; Lim, Jae-Han; Song, Seung-Yeong
Abstract: To achieve national greenhouse gas reduction in the building sector, heating and cooling energy in buildings should be reduced. The government has strengthened regulations on insulation performance for building energy savings. However, the building envelope has various thermal bridges. In particular, a metal panel curtain wall comprises a number of thermal bridges at joints between the panels and the fixing units, thus degrading the overall thermal performance. To reduce building energy, it is necessary to reduce thermal bridges in building envelopes. This study aims to analyze the energy saving potential achieved by reducing thermal bridges. For this, the insulation performance and building energy needs of the existing and alternative metal panel curtain wall were evaluated. The alternative metal panel curtain wall that uses plastic molds at joints between panels and the thermally-broken brackets was suggested to reduce heat loss through thermal bridges. As results, the effective U-value of the alternative metal panel curtain wall was reduced by 72% compared with the existing metal panel curtain wall. In addition, annual heating energy needs of the alternative metal panel curtain wall building was reduced by 26%, and annual total energy needs was reduced by 6% because annual cooling energy needs of it slightly increased compared with the existing metal panel curtain wall. In conclusion, the alternative metal panel curtain wall considerably influenced the savings in building energy needs by reducing thermal bridges.